2010
DOI: 10.1038/nphoton.2010.119
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared optical parametric amplifier using silicon nanophotonic waveguides

Abstract: All-optical signal processing is envisioned as an approach to dramatically decrease power consumption and speed up performance of next-generation optical telecommunications networks 1-3 . Nonlinear optical effects, such as four-wave mixing (FWM) and parametric gain, have long been explored to realize all-optical functions in glass fibers 4 . An alternative approach is to employ nanoscale engineering of silicon waveguides to enhance the optical nonlinearities by up to five orders of magnitude 5 , enabling integ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
274
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 407 publications
(282 citation statements)
references
References 30 publications
3
274
5
Order By: Relevance
“…Moreover, a frequency up-shifted Raman anti-Stokes [15] peak at a wavelength of 1950 nm is visible. The visibility here of a strong MI background suggests that the on-chip mid-IR parametric gain available is far larger than demonstrated in previous studies [1], where MI was not observed. As illustrated in Fig.…”
Section: Broadband Modulation Instability and Raman-enhanced Fwmcontrasting
confidence: 60%
See 3 more Smart Citations
“…Moreover, a frequency up-shifted Raman anti-Stokes [15] peak at a wavelength of 1950 nm is visible. The visibility here of a strong MI background suggests that the on-chip mid-IR parametric gain available is far larger than demonstrated in previous studies [1], where MI was not observed. As illustrated in Fig.…”
Section: Broadband Modulation Instability and Raman-enhanced Fwmcontrasting
confidence: 60%
“…Moreover, we demonstrate that on-chip gain can exceed 50 dB in narrow bands assisted by stimulated Raman scattering. In comparison with prior work [1], the peak operating pump power is reduced to less than half. At the same time, the maximum on-chip gain obtained using the 2 cm-long wire here shows an improvement of more than 25 dB, while the on-chip gain bandwidth (> 580 nm) is increased by more than 2.5x.…”
Section: Broadband Modulation Instability and Raman-enhanced Fwmmentioning
confidence: 68%
See 2 more Smart Citations
“…The fact that many impressive all-optical demonstrations have been made in silicon despite its low FOM is a testament to how exceptional its linear and nonlinear optical properties are. Nonetheless, the critical impact of silicon's large TPA was illustrated [48,49] in 2010 by the demonstration of high parametric gain at wavelengths beyond 2 µm, where TPA vanishes. Indeed, it is likely that in the midinfrared wavelength range where it is transparent to both one photon and two photon transitions -between 2 and 6 µm -silicon will undoubtedly remain a highly attractive platform for nonlinear photonics.…”
Section: Introductionmentioning
confidence: 99%